Travel to Southeast Asia: Learning About Southeast Asia through Augmented Reality - Siti Zalifah Ramli; Siti Aishah Zahari; Nur Amalia Atikah Edyanto; Muhammad Asyraf Abdullah Zawawi; Nur Ain Najihah Ibharim (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
‘Travel to Southeast Asia’ application is one of Augmented Reality (AR) technology. Learn about Southeast Asia is very important and has been emphasized in high schools. However, there are some students who are bored and not interested in learning geography especially related to foreign countries due to lack of exposure and information about it. So, the main purpose of this project is to develop an educational application based on Augmented Reality for students to interest them in learning about Southeast Asia. Students also can identify eleven countries in Southeast Asia by using this application and gain some knowledge related to the countries. Unity software is the main software to develop this Augmented Reality because Unity engine can support the high quality of audio and visual effects to ease the development of the project. This project developed by using ADDIE Model as a dynamic and flexible guideline for building effective training and performance support tools. This research was evaluated by among 15 students from Sultan Idris Education University who pursuing a Bachelor of Education (Geography) with Honor by using quantitative methods through online questionnaire. This questionnaire was distributed to the respondents for evaluation based on Usefulness, Satisfaction and Ease of Use (USE) questionnaire. As a result of the questionnaire, majority of respondents gave positive feedback and interested with ‘Travel to Southeast Asia’ application. Based on the research, learning about Southeast Asia using Augmented Reality provides better knowledge and understanding.